Collaboration training: Composting organic waste with Karang Taruna and Kanreapia Youth Organization - Amansyah, Munawir; Syarif, Alwiyah Nur; Berlian, Berlian; Elvira, Elva; Ramadan, Fitrah (Sociality: Journal of Public Health Service, 2024)
Globally, waste production continues to increase along with population growth and consumption. This has caused serious problems related to waste management in many areas. Including in Halahalaya Hamlet, Kanreapia Village where waste that is not managed properly can threaten human health, the environment and the sustainability of natural resources. To reduce the accumulation of waste, the community needs to be empowered and equipped with waste processing methods with the younger generation as their representatives. So that this is the goal to be achieved in this activity. The methods used in this program are counselling and demonstration. All training participants are members of two internal organizations, namely Karang Taruna and IPMAH Kanreapia Organization who live in Halahalaya Hamlet, Kanreapia Village, Tombolo Pao District, Gowa Regency, with a total of 9 people. Data analysis was carried out descriptively by looking at the average pre and post test scores. From the results of the analysis, it was concluded that there was an increase in knowledge before counselling was given and after counselling, where before counselling with an average value of 47.78 then after counselling became 62.22, this showed the success of counselling on the use of organic waste carried out.